1975
DOI: 10.1111/j.1471-0528.1975.tb02216.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Metabolism in the Menstrual Cycle

Abstract: Summary Blood sugar, serum insulin and growth hormone levels in response to 100 g. of oral glucose were studied under carefully controlled conditions on days 9, 18 and 27 of the menstrual cycle in 20 healthy women aged 18 to 20 years. The results indicate that blood sugar and serum insulin levels in response to oral glucose loading do not alter significantly in the menstrual cycle. Seven of the women had repeat studies on the same days three cycles later. No significant change in blood sugar or serum insulin l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1978
1978
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Thus, this hypothesis cannot be supported from the literature. This is due to the fact that most reports describing the metabolic consequences of combined estrogen/progestagen OC do not take into consideration the day of the cycle used to perform control studies (28)(29)(30)(31)(32), perhaps because some authors have found no difference in glucose tolerance and insulin sensitivity during the menstrual cycle (33,34). In contrast, other investigators have described differences during the cycle, with lower glucose tolerance in the luteal than in the follicular phase (35,36).…”
mentioning
confidence: 71%
“…Thus, this hypothesis cannot be supported from the literature. This is due to the fact that most reports describing the metabolic consequences of combined estrogen/progestagen OC do not take into consideration the day of the cycle used to perform control studies (28)(29)(30)(31)(32), perhaps because some authors have found no difference in glucose tolerance and insulin sensitivity during the menstrual cycle (33,34). In contrast, other investigators have described differences during the cycle, with lower glucose tolerance in the luteal than in the follicular phase (35,36).…”
mentioning
confidence: 71%
“…In healthy nondiabetic women, some investigators have reported a worsening in glucose tolerance, as assessed by the oral glucose tolerance test (OGTT), during the luteal phase (4,5). However, other studies that used the OGTT (6,7) or the intravenous glucose tolerance test (8) did not find significant changes in glucose tolerance or insulin concentration as a function of the menstrual cycle phase. Evaluation of insulin sensitivity by means of the euglycemic-hyperinsulinemic clamp technique has also failed to detect alterations during the luteal phase in nondiabetic women (9,10).…”
mentioning
confidence: 95%
“…In contrast, studies measuring glucose and insulin responses to an OGTT 30 , 40 or to an IVGTT, 28 , 29 as well as insulin‐mediated glucose disposal using the euglycemic hyperinsulinemic clamp technique, 41 43 have shown no differences between follicular and luteal cycle phases in healthy women. Similarly, in the current study, premenopausal women evidenced no luteal phase abnormality in glucose tolerance as assessed by OGTT.…”
Section: Resultsmentioning
confidence: 98%
“…Previous cross‐sectional reports on glucose metabolism in relation to the menstrual cycle have shown conflicting results. While most studies found no cycle‐related change in fasting glucose values, 28 – 30 Billig 31 noted a decrease, while Okey, in a longitudinal study, 32 found an increase in FPG during the luteal phase. An OGTT‐associated decline in glucose tolerance during the luteal phase of healthy women was reported by Peppler, 33 Jarrett, 34 and Fioretti 35 .…”
Section: Resultsmentioning
confidence: 98%